Interactive Smart Book Design Based on Augmented Reality with Constructivism Approach in Introduction to Management Course - Siti Kholifah; Hendri Rasminto (LPPM Universitas PGRI Semarang, 2025)
In Indonesia, there are no augmented reality-based management economics textbooks yet, most of them are still ordinary printed management economics books. In the previous introductory management course book, it was still a regular printed book, there was no touch of augmented reality technology so that the product of the introductory management course was still simple, then after conducting interviews with the lecturers of the introductory management course, an interactive smartbook based on augmented reality with a constructivist approach will be developed in the introductory management course using the ADDIE model, The research method uses the ADDIE model which is implemented holistically from the analysis, design, development, implementation and evaluation stages, and has been assessed by the validation of learning media experts by 98% and learning material experts by 87.5%, then an interesting introductory management book was produced with its augmented reality and was accepted by students with an assessment score of 92.75% meaning that this interactive smartbook product is very suitable for use in introductory management learning.